EVALUACIÓN DE UN MÉTODO DE SECADO EN UN FILETE DE LA ESPECIE CORVINA (Argyrosomus regius) MEDIANTE INMERSIÓN EN SALES - Ayala Zambrano, Ailyn Lilibeth (2023)
This thesis focuses on the "Evaluation of a Drying Method on a Fillet of the Corvina Species (Argyrosomus regius) by Immersion in Salts." To evaluate the Immersion Time in Brine between (8h, 16h and 24h) it was carried out an exhaustive evaluation to determine the optimal brine immersion time in the processing of croaker fillets (Argyrosomus regius). This step was essential to achieve effective drying and preserve the quality of the product. The ideal combination of drying times was established between 2h and 3h and temperature between (120 °C and 125 °C) to obtain an optimal level of drying in the sea bass fillets. This aspect is essential to guarantee food safety and the quality of the final product. By determining the temperature optimal and the time necessary to obtain a good level of drying, it has been possible to identify that a temperature of 120 °C for 2 hours, this being the b0 and c0 factor, guarantees an adequate reduction of humidity in the product and as for the evaluation of moisture loss at temperatures of 120°C and 125°C, with data taken weight in grams vs. time in minutes, obtaining negative slopes, since the lines are descending, applied to two temperatures that were 125 °C and 120 ° C, we can determine that the first applied temperature resulted in the slope, the highest and lowest value were: -0.8236 (16h of immersion and 2h of drying) and -0.9428 (8h of immersion and 3h of drying). In the second temperature, the highest and lowest values were: -0.8636 (24 hours of immersion and 2 hours of drying) and -0.9702 (8 hours of immersion and 3 hours of drying. This research contributes significantly to the knowledge about drying methods in the fish processing industry, with a specific focus on the Corvina species (Argyrosomus regius).